2008
DOI: 10.1159/000172086
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 11p14-p12 deletion in WAGR syndrome by array CGH for identifying genes contributing to mental retardation and autism

Abstract: WAGR (Wilms tumor, Aniridia, Genitourinary malformations and mental Retardation) syndrome is a rare genomic disorder caused by deletion of the 11p14-p12 chromosome region. The majority of WAGR patients have mental retardation and behavioral problems, and more than 20% of the patients also have features of autism. While the Wilms tumor/genitourinary anomalies and aniridia are caused by deletion of WT1 and PAX6 respectively, the genomic cause of mental retardation and autism in WAGR syndrome remains unknown. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 46 publications
6
76
0
4
Order By: Relevance
“…3,4 A variety of dysmorphic features and behavioural, neurological and metabolic abnormalities, including obesity, may also be present. 3,23,24 MOLECULAR AND GENETIC BASIS OF ANIRIDIA Loss of function of one copy of the PAX6 gene can be identified in about 90% of aniridia cases, with intragenic mutations accounting for two-thirds and chromosomal rearrangements for one-third of cases. 4,25 About two-thirds of all cases are familial and show dominant inheritance with very-high penetrance.…”
Section: Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 A variety of dysmorphic features and behavioural, neurological and metabolic abnormalities, including obesity, may also be present. 3,23,24 MOLECULAR AND GENETIC BASIS OF ANIRIDIA Loss of function of one copy of the PAX6 gene can be identified in about 90% of aniridia cases, with intragenic mutations accounting for two-thirds and chromosomal rearrangements for one-third of cases. 4,25 About two-thirds of all cases are familial and show dominant inheritance with very-high penetrance.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…The phenotypic spectrum is determined by the identity of the genes in the deletion. 3,23,24 Reproductive transmission is thus significantly reduced. Larger WAGR deletions therefore generally arise de novo in each case, and siblings are unlikely to be affected, although rare cases of balanced translocations in a parent can lead to recurrent larger deletions.…”
Section: Clinical Workupmentioning
confidence: 99%
“…In this study, we performed an extensive functional analysis of COM MD9, a COM MD family member that is frequently deleted in WAGR syndrome (MIM 194072), a congenital condition caused by a microdeletion and haploinsufficiency at 11p13 (Xu et al, 2008). We report that COM MD9 is incorporated into the CCC complex and plays a critical role in endosomal sorting of Notch family members.…”
Section: Endosomal Sorting Of Notch Receptors Through Com Md9-dependementioning
confidence: 99%
“…Human PAX6 gene is originally identified in chromosomal region 11p13 as one related with WAGR (Wilm's tumor, Aniridia, Genitourinary malformations and mental Retardation) syndrome [18,19], which is a rare genetic disorder caused by chromosomal deletion of the 11p12-p14 region. The majority of WAGR patients have mental retardation and behavioral problems, and importantly, more than 20% of the patients also have features of autism [20,21]. Recent studies have identified PAX6 mutations in individuals who manifest mental retardation, aniridia and autism [22][23][24].…”
Section: Introductionmentioning
confidence: 99%